Spatial assessment of soil fertility index on tropical mineral soil across land units in Padayo farming community, West Sumatra - Hijri, Nurul; Reflinaldon, Reflinaldon; Hermansah, Hermansah; Juniarti, Juniarti; Harianti, Mimien; Noferita, Jelsi Trisna; Khairati, Nurul; Naspendra, Zuldadan; Ivanovich, Vasenev Ivan (Journal of Degraded and Mining Lands Management, 2026)
Soil fertility is one of the primary aspects determining agricultural productivity, especially in tropical mineral soils, where nutrient constraints frequently limit crop growth and yield. This study aimed to (a) assess and map the Soil Fertility Index (SFI) across different land units, (b) evaluate soil characteristics, and (c) analyze the major factors influencing soil fertility. A total of 21 soil samples from 14 land units were studied. The SFI was calculated using seven key soil chemical properties: pH, organic matter, phosphorus, potassium, calcium, magnesium, and aluminum. The results showed that soil fertility in the study area was generally low, with a mean SFI value of 21.53. Among the land units, two were classified as very low, nine as low, and three as moderate fertility. The lowest SFI (16.14) was observed in land unit pTls.2.Kc, while the highest (26.78) occurred in pTps.2.Hs. Only 34.50% of the area exhibited moderate fertility, with the remainder classified as low to very low. Principal component analysis revealed that four components accounted for 81.36% of the total variance, with the dominant factors ranked as follows: CEC>base saturation>aluminum saturation>K>Mg>Ca>Na>P>pH>soil organic carbon. High annual rainfall (5,064 mm/year) and predominantly moderately steep to steep slopes were the main agroclimatic and physical constraints limiting land use. The study highlighted that the SFI is effective in representing soil fertility status in tropical soils. The integration of suitable crops that are adapted to ecological conditions and the improvement of soil fertility based on key controlling factors are essential for utilizing the land.